Synergistic Effect of Some Inorganic Corrosion Inhibitors for Carbon Steel in Cooling Water - Hussein, Mudhaffar Y.; J.Mohammed, Haider; Nagy, Alaa A. (Basrah Journal for Engineering Sciences, 2012)
The current approach to cooling water treatment is to use a multi – component inhibitors. Cooling water formulations containing mixtures of inhibitors usually offer better and increased protection to ferrous metals than similar concentrations of either of the individual components. Such mixtures are synergistic in their action .But; the synergistic effects between nitrites, molybdates and inorganic phosphate were not investigated until recently. A weight loss technique was used to investigate such mixture and to optimize the concentrations of the components in the blend.Consequently; an efficient and effective blend was developed as a corrosion inhibitor for carbon steel in aerated Al–Daura refinery re-circulating cooling water in the pH range 6.75 to 7.25. The preferred concentrations of components in the multi- component inhibitor blend (as ppm ) were: (SN + SM): SHMP = 800: 20 with SN: SM weight ratio =3:2.The reduction in corrosion rate was 97.6 % .